2018
DOI: 10.7759/cureus.2114
|View full text |Cite
|
Sign up to set email alerts
|

Morphine, Oxygen, Nitrates, and Mortality Reducing Pharmacological Treatment for Acute Coronary Syndrome: An Evidence-based Review

Abstract: Since it was first reported in 1912, acute coronary syndrome (ACS) has become the leading cause of death in the Western world. Several improvements that have been made over the years in the pharmacological treatment of ACS have reduced the relative risk of death due to myocardial infarction from 35-45% previously to approximately 3.5% at present. Universities, websites, and educational videos commonly use a mnemonic for morphine, oxygen, nitrates, and aspirin (MONA) to refer to the adjuvant treatment used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…Nowadays, there are concerns that this approach might be obsolete and inappropriate. 25 A similar approach, warranting high SaO 2 targets, was also evident in the current survey for patients in the early period post-cardiac arrest.…”
Section: Articlesupporting
confidence: 54%
“…Nowadays, there are concerns that this approach might be obsolete and inappropriate. 25 A similar approach, warranting high SaO 2 targets, was also evident in the current survey for patients in the early period post-cardiac arrest.…”
Section: Articlesupporting
confidence: 54%
“…Nitrates are exogenous donors of NO that have been used for more than 130 years history and are among the most widely used anti-myocardial ischemia drugs. Several clinical trials demonstrated that nitrates reduce infarct size in combination with thrombolytic therapy, but most results were negative and even indicated reverse outcomes [16,17]. In addition, there is no published experimental or clinical study focused on nitrate postconditioning.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have noted an increased mortality risk in heart failure patients receiving morphine [35][36][37]. Morphine provides analgesic benefits in patients with myocardial infarction, and it decreases blood pressure and anterior brachial mean pressure in these patients.…”
Section: Opioids In a Nutshell And Controversies Surrounding The Use mentioning
confidence: 99%